SINTESIS 7-FORMILINDOL SEBAGAI BAHAN DASAR PEMBENTUK KATALIS EPOKSIDASI BARU (Synthesis Of 7-Formylindole As Precursor Of New Epoxidation Catalysts) - Sholihin, Hayat (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2001)
Manganese (III) salen complexes have been reported as epoxidation catalysts. It is caused a major breakthrough in the enantioselective epoxidation of alkenes into epoxide compounds. This catalyst was synthesized from salicylaldehyde derivatives. Based on the structure, salicylaldehyde is an isosteric nature of 7-folmylindole, consequently opened the door to an array of fascinating and versatile ligand systems, and offer tremendous scope for molecular designe, because of the greatly enhanced capacity for substitution of indoles compared with phenols. Initial target of the project to synthesize of 7-formylindole. There are numerous strategies and methodes to achieve the target molecules. Further study of reaction mechanism of a useful target compound could be explanated and developed as a new class of catalyst.